ANALISIS DIVERSIFIKASI PRODUK TAHU UNTUK MENINGKATKAN DAYA SAING PRODUK - Endang Siswati; Ardi Ardana; Juliani Pudjowati (Unitri Press, 2022)
This research is a descriptive qualitative research that aims to analyze the diversification of tofu products and the factors that encourage it. The research location is in the tofu company, Mrs. Mujiani, Tropodo village, Krian sub-district. The informants in this study were the tofu business owner, Mrs. Mujiani, an employee of the production department, a customer, and a customer of a competitor's product. After the data was taken and checked for validity with triangulation methods including data triangulation, source, and technique triangulation, then data analysis was carried out. The results of the analysis are that the product diversification at Mrs. Mujiani's tofu company is in the tofu variants, namely fried tofu, half-cooked Chinese tofu and raw Chinese tofu, after product diversification there is an increase in sales so that the company's income also increases, this can increase product competitiveness in the market. . Whereas the driving factors for product diversification are, among others, the company wants to increase sales turnover so that profits can increase, increase distributors or salespeople, reduce production costs so that efficiency and effectiveness are obtained, employees become solid and strong, and are driven by the desire to use large capacity machines.